Brain signal changes of sensory cortex according to surface roughness of boneless corsets. Issue 1 (January 2020) - Yuan, Jie; Xu, Changliang; Wang, Qicai; Yu, Weidong
The tactile perception of fabric surface properties in the brain has always been a major research issue in the study of the contact comfort of fabrics. This study introduced the concept of PSC (percent signal change) obtained by fMRI (functional Magnetic Resonance Imaging) technology to explore the perceptual brain regions concerned with the roughness of the fabric surface. Firstly, the PSCs of human somatosensory cortexes, including the SI (primary somatosensory cortex) and SII (secondary somatosensory cortex), under the stimulation of boneless corsets with different surface roughness, were extracted and analyzed. As the surface roughness of the fabric increased gradually from smooth to rough, the brain region in which the maximum PSC occurred gradually transited from the SI to the SII, which indicated that the SI brain region paid more attention to the contact of smooth fabrics, while the SII brain region laid emphasis on the fine tactile perception of rough fabrics. Furthermore, the result of sub-regions in the SI and SII showed that, with the increase of the roughness of the fabric surface, the PSC of the OP2 (Operculum Parietal 2) brain region increased significantly, and the brain region concerned with the fabric surface tactile stimulation was gradually transferred from the slow adaptive sensory projection Brain Area 3a in the SI to the fast adaptive sensory projection Brain Area 1 in the SI, and finally moved to OP2 in the deep cortex of the SII.